Territorial differences of the life quality, as a complex indicator in Germany and Hungary - Dora Szendi (DETUROPE)
In the last three decades the analyses of convergence are in the foreground of the empirical analysis. Most of the empirical works examine the realization of convergence according the GDP indicator. In the author’s opinion in some cases the GDP-based analyses do not indicate the changes of the social processes. That is why the author suggests in this recent research the use of a complex indicator to measure the inequalities of the life quality. The aim of the analysis is twofold. First to examine the spatial characteristics of the life quality compared to the GDP, and second to analyse the neighbourhood relations with the use of spatial autocorrelation methods.